Market driven network neutrality and the fallacy of a two-tiered Internet traffic regulation - Günter Knieps; Volker Stocker (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2014)
Within a Generalized DiffServ architecture entrepreneurial flexibility for building intelligent multipurpose traffic architectures enables the provision of a variety of tailored traffic services for a wide range of heterogeneous application services. In order to solve the entrepreneurial traffic capacity allocation problem, we propose an incentive compatible pricing and quality of service (QoS) differentiation model for the Generalized DiffServ architecture resulting in market driven network neutrality. Optimal allocation decisions based on the opportunity costs of capacity usage require that all relevant traffic classes are taken into account simultaneously, rather than 1) excluding traffic classes (by means of minimum traffic quality requirements), 2) prescribing a maximum or minimum number of traffic classes or 3) arbitrarily including parameter specifications for or levels of QoS which are not reflected by demand side. It is particularly important that the opportunity costs of capacity reservations for deterministic premium traffic classes are interrelated with subsequent non-deterministic traffic classes. As a consequence, every form of market split would be artificial.
Keywords: 330